Southeast Asian ecological dependency on Tibetan Plateau streamflow over the last millennium - Chen, Feng; Man, Wenmin; Wang, Shijie; Esper, Jan; Meko, David; Büntgen, Ulf; Yuan, Yujiang; Hadad, Martín; Hu, Mao; Zhao, Xiaoen; Roig, Fidel A.; Fang, Ouya; et al. (Nature geoscience, 2023)
The great river systems originating from the Tibetan Plateau are pivotal for the wellbeing of more than half the global population. Our understanding of historical ranges and future changes in water availability for much of Southeast Asia is, however, limited by short observational records and complex environmental factors. Here we present annually resolved and absolutely dated tree ring-based streamflow reconstructions for the Mekong, Salween and Yarlung Tsangpo rivers since 1000 ce , which are supplemented by corresponding model projections until 2100 ce . We show a significant positive correlation between streamflow and dry season vegetation indices over the Indochinese Peninsula, revealing the importance of the Tibetan Water Tower for the functioning and productivity of ecological and societal systems in Southeast Asia. The streamflow variability is associated with low-frequency sea-surface temperature variability in the North Atlantic and North Pacific. We find that streamflow extremes coincide with distinct shifts in local populations that occurred during medieval times, including the occupation and subsequent collapse of Angkor Wat from the eleventh to the sixteenth century. Finally, our projections suggest that future streamflow changes will reach, or even exceed, historical ranges by the end of this century, posing unprecedented risks for Southeast Asia. Reconstructions of Tibetan Plateau streamflow over the last millennia reveal close associations with dry season vegetation and major population shifts in Southeast Asia.